THE EFFECT OF USING PICTURE STORY BOOK TO INCREASE STUDENTS’ READING COMPREHENSION IN CLASS 10 SMA NEGERI 1 TONDANO - Ni Luh Parwati; Nihta Liando; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2022)
The goal from these learn was to investigate whether picture story book can increase reading comprehension or not. The course in this study were 30 students from Classroom 10 Science2 in SMA Negeri 1 Tondano. This type of research was quantitative with Experimental design with pre-test and post-test design. Data obtained from pre-test and post-test is collected using multiple choice and essay test consisting of 20 items. With the number of multiple choice questions 10 numbers and 10 number essays. The results of this study showed that there was a significant achievement between pre-test and post-test. The highest score obtained by students on the pre-test is 60 and the highest score obtained by students on the post-test is 90. It can be concluded that the used of picture story book can increase students' reading comprehension. English teachers are advised to use picture story book at SMA Negeri 1 Tondano because using picture story book can increase students' reading comprehension